2017
DOI: 10.1158/1538-7445.sabcs16-p4-19-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-19-06: Return to work after breast cancer diagnosis: An observational prospective study of 125 patients in South America

Abstract: Background:Breast cancer is the most common cancer in women. While its incidence has been increasing, recurrence and mortality rates have been decreasing. Because of that, cancer can now be regarded as a transient shock that does not prevent the survivors to live normal lives, including returning to their workplace. From a social perspective, long periods of sick leave have a strong economic impact. From the patient perspective, prolonged sick leave can cause financial difficulties and emotional distress. In U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, BC has a strong economic impact, especially in young patients, as the majority of women < 54 years are economically active [62] and prolonged sick leave can cause financial difficulties and emotional distress [63]. An observational study in a third-level hospital in Brazil evaluating return to work rates in BC patients 18–57 years old found that although 61.5% received support from their employers, only 29.1% reported adjustment offering so that they could keep working during treatment [63]. Overall, 22.1% and 28.8% of patients had returned to work at 6 and 12 months after BC diagnosis, respectively.…”
Section: Burden Of Advanced Disease In Young Womenmentioning
confidence: 99%
“…Additionally, BC has a strong economic impact, especially in young patients, as the majority of women < 54 years are economically active [62] and prolonged sick leave can cause financial difficulties and emotional distress [63]. An observational study in a third-level hospital in Brazil evaluating return to work rates in BC patients 18–57 years old found that although 61.5% received support from their employers, only 29.1% reported adjustment offering so that they could keep working during treatment [63]. Overall, 22.1% and 28.8% of patients had returned to work at 6 and 12 months after BC diagnosis, respectively.…”
Section: Burden Of Advanced Disease In Young Womenmentioning
confidence: 99%